The Role of Educational Guidance Strategies in Modifying The Behavior of Public School Students in Ajloun Governorate from The Point of View of Principals - Kharabsheh, Suha Mohammad Eid (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of educational guidance strategies in modifying the behavior of public school students in Ajloun governorate from the point of view of principals. The researcher used the Descriptive approaches, study Sample consisted from (100) Female and male principals, chosen randomly, to collect data Questioner used, which consisted (34) paragraph. The result of SPSS analysis shown that the degree of the role of educational guidance strategies in modifying the behavior of public school students in Ajloun governorate from the point of view of principals was High with average (3.68 out of 5), The finding also showed there was statistically significant differences at (α≤0.05) refers to principals sex (male and female) in favor of female. In addition, there were no statistically significant differences refers to principals years of experience.